Catalytic Insights of Copper(I) Complexes with Phosphole Ligands in Three-Component Reactions to Produce Propargylamines and 1,4-Substituted 1,2,3-Triazoles. - Garcia-Garfido, J (Elsevier B.V., 2024)
The catalytic activity of two complexes, 2a ([CuCl{k1(P)-1a}{k2(P,N)-1a}]; 1a = 2,5-bis(2-pyridyl)-1-phenylphosphole) and 2b ([CuCl{k1(P)-1b}2]; 1b = 2,5-bis(2-thienyl)-1-phenylphosphole), was investigated in three-component reactions for the synthesis of propargylamines and 1,4-substituted 1,2,3-triazoles. This article introduces the first-time synthesis and characterization of complex 2a, while complex 2b has been previously reported by us. An X-ray crystallographic analysis revealed that the copper(I) complex 2a exhibits a pseudo-tetrahedral geometry with two phosphole ligands demonstrating k1(P)- and k2(P,N)-coordination, in contrast to complex 2b, which adopts a trigonal planar geometry. In a solution environment, 1a exhibits hemilability, leading to a dynamic equilibrium between the tetra-coordinated complex (2a) and its tri-coordinated counterpart (2a’). This behavior is substantiated by theoretical calculations, which confirm a preference for the tetra-coordinated geometry. Regarding catalytic activity, 2a and 2b exhibited effective catalytic activity in A3-coupling reactions and the direct synthesis of 1,4-disubstituted 1,2,3-triazoles. However, 2b demonstrated superior catalytic performance in both reactions compared to 2a. Theoretical calculations suggest that the stronger N–Cu σ-bond in 2a hinders the interaction of the alkyne with the copper center, whereas the trigonal planar geometry of 2b facilitates better copper-alkyne π-interactions. © 2024